Morfologia do tubo digestivo nos cupins Heterotermes tenuis (Hagen) e Coptotermes havilandi Holmgren (Isoptera, Rhinotermitidae) - Barsotti, Raquel Cristina [UNESP]; Costa-Leonardo, Ana Maria [UNESP] (Sociedade Brasileira de Zoologia, 2000)
The digestive tube of workers of Heterotermes tenuis (Hagen, 1858) e Coptotermes havilandi Holmgren, 1911 was analysed under the anatomical view. The digestive tube of both species did not show conspicuous diferences in relation to the morphology, morphometry and the configuration of the digestive tube that were the aspects studied. The general organization of the digestive tube of these species show several similarity with other lower termites previously analysed.
Morphology of the digestive tube in the termites Heterotermes tenuis (Hagen) e Coptotermes havilandi Holmgren (Isoptera, Rhinotermitidae)
Keywords: Isoptera; Heterotermes tenuis; Coptotermes havilandi; digestive tube